(Re) Reading Mishima Reading Sade: An Aesthetics of Transgressive Feminine Sexuality - BAŞ, IŞIL (My University, 2019)
A recurrent internovelistic theme in the work of Japanese writer Yukio Mishima is the threat of insidious, emasculating feminine sexuality and cruelty set against an idealized and purified femininity.However, in the play Madame de Sade (1965) Mishima seems to reveal a much more complex vision of feminine agency and sexuality from the fictional perspective of real women characters in Marquis de Sade's life. This paper will reread Mishima's play in the context of Simone de Beavoir's Must We Burn Sade and Angela Carter's The Sadeian Women both of which refuse to see in Sade a misogynistic, animalistic and banal cruelty.